Relevansi Nilai-Nilai Piagam Madinah terhadap Sistem Hukum Nasional Indonesia : Tinjauan atas Perlindungan Hak Minoritas dan Kebebasan Beragama - syakira; Siti Hawa Nabilla; Marzuki (STIH Zainul Hasan Kraksaan Kraksaan, 2026)
This article examines the political orientation in the Medina era as a foundational model for Islamic governance, focusing on its enduring relevance to contemporary legal frameworks. It addresses the critical need to understand how the Prophet Muhammad SAW established a political structure rooted in Islamic values that effectively accommodated the diverse elements of Medina society. The primary objective of this study is to analyze the relevance of the Piagam Madinah's values in the formation of Indonesia's national legal system, particularly concerning the protection of minority rights and religious freedom. Employing a qualitative literature study with a historical-analytical approach, the research draws from primary Islamic sources (Qur'an, hadith) and contemporary scholarly works on Islamic political thought, complemented by analysis of Indonesian legal frameworks, constitutional law, and studies on human rights and religious pluralism in Indonesia. The findings demonstrate that the Prophet Muhammad successfully laid down political principles emphasizing brotherhood (al-Ikha), compassion (al-Mahabbah), justice (al-Adalah), and equality (al-Musawa). The conclusion asserts that these universal values from the Piagam Madinah align significantly with Indonesia's Pancasila and the 1945 Constitution, offering profound ethical and philosophical inspiration for an inclusive national legal system committed to religious freedom and minority protection.